Case Report: Unmasking an anomalous coronary artery during emergency STEMI intervention: a rare diagnostic challenge with successful revascularization outcome - Muhammad Saad Reihan; Tarek Ahmed Ahmed Dabash; Ahmed Mohammed Ahmed Mostafa; Mohammed Ali Mohammed Hammad; Husna Irfan Thalib; Hamdy Abdelazeem Elkafory; Mohammed Moanes Mohammed Mohyeldin (Frontiers in Cardiovascular Medicine, 2026)
Background Coronary artery anomalies during primary PCI are uncommon but can increase procedural complexity and delay reperfusion in STEMI. Anomalous origin of the right coronary artery (RCA) from the left coronary cusp is a rare congenital variant that poses diagnostic and technical challenges in emergency intervention. Case presentation A 39-year-old female with insulin-dependent diabetes presented with 10-hour chest pain, diaphoresis, and dyspnea. She was in acute pulmonary edema (Killip III) with sinus tachycardia. ECG showed extensive anterior STEMI, and troponin exceeded 50,000 ng/L. Echocardiography revealed LVEF 39% with apical hypokinesia. She received standard STEMI therapy and underwent urgent PCI. Radial access failed due to spasm, requiring femoral crossover. Angiography showed proximal LAD occlusion (TIMI 0) and difficulty engaging the RCA. Non-selective aortic cusp injection revealed anomalous RCA origin from the left coronary cusp. Primary PCI to the LAD was performed with a drug-eluting stent, restoring TIMI 3 flow. Door-to-wire time was 52 min and fluoroscopy time 11.5 min. The patient improved clinically, with troponin reduction to 26,000 ng/L and discharge after 5 days. At 1-month follow-up, LVEF improved to 45%. Conclusion Anomalous RCA origin from the left coronary cusp is a rare but critical finding in STEMI PCI. Early recognition and adaptive catheter strategy are essential to avoid delay and ensure successful reperfusion.